PENGARUH PEMBERIAN JUS TOMAT TERHADAP TEKANAN DARAH LANSIA PENDERITA HIPERTENSI DIDESA LEMAHIRENG KECAMATAN BAWEN - Blessa Adhy Nugraha (Jurnal Ilmu Keperawatan Komunitas, 2018)
Hypertension is the most common disease in the elderly and causes death worldwide every year. Hypertension disease can be controlled non pharmacologically.Objective: To know the effect of tomato juice to blood pressure of elderly hypertension patients in Lemahireng Village, Bawen Sub-district. Methods: This type of research wasQuasy Experiment using one - group pre post test design. The population was 60 elderlywho suffering hypertension in Lemahireng village, samples in this study were  15 people. Sampling was Non-random tehnique and used accidental method. The research done in 6-13 February 2018. Blood pressure was measured using a sphygmomanometer. Data analysis used dependentt-test(α = 0,05) Results:In the tomato juice group, the average systole before administeringtomato juice was 164.47 and after it was 150.53 mmHg, whereas diastole before administering tomato juice was 93.00 and 85.53 mmHg afterwards.Discussion:Tomato juice has benefit to lower blood presure due to Kalium as barrier renin secretion so its increasing in water and natrium.Kalium influences in renin angiotension to lower potential membran in blood vessel so become relax . Conclusion: There is effect ofadministering tomato juice to lower blood pressure